Molecular characterisation of Theileria equi and risk factors associated with the occurrence of theileriosis in horses of Punjab (Pakistan). (11th August 2019) - Ali, S.; Ijaz, M.; Farooqi, S. H.; Durrani, A. Z.; Rashid, M. I.; Ghaffar, A.; Ali, A.; Rehman, A.; Aslam, S.; Khan, I.; Masud, A.; Mehmood, K.
Summary: Theileria equi ( T. equi ) is an obligate intra‐ and extra‐erythrocytic parasite that causes equine theileriosis (ET) in equids. Equine theileriosis is considered a notifiable disease of global significance, a major constraint to the international movement of horses, and endemic in many countries. This disease may be difficult to diagnose, as it can produce variable and nonspecific clinical signs. A cross‐sectional study was designed for the molecular characterisation of T. equi and to investigate the associated risk factors of ET accompanied by its consequences on haematological and sero‐biochemical parameters. A convenience sampling of 500 blood samples were collected from ET suspect horses from January to December 2017. PCR was performed on all blood samples targeting the 18S rRNA gene of T. equi followed by sequencing; 9% animals tested positive with confirmed sequences. The isolates of this study showed high homology with Cuban, Russian and Brazilian isolates of T. equi (accession numbers KY111762.2, MG551915.1 and KY952237.1, respectively). Based on multivariate analysis, the principal risk factors consisted of absence of dogs on the premises and presence of tick infestation. The haemato‐biochemical parameters showed a decrease in granulocytes and erythrocytes, and an increase in lymphocytes, monocytes, mean corpuscular volume, mean corpuscular haemoglobin, mean platelet volume, glucose, phosphorus and aspartate aminotransferase in positive horses. This is the first study which identified ET in Punjab (Pakistan) using molecular techniques and risk factors together with the haemato‐biochemical variations in horses.